Microspherical high-entropy spinel type ferrite wave-absorbing material and preparation method thereof
By using microspherical high-entropy spinel type ferrite absorbing materials, the problems of limited reflection loss value and narrow effective absorption bandwidth of existing ferrite materials are solved, and efficient electromagnetic wave absorption and broadband performance are achieved, meeting the electromagnetic wave pollution prevention and control needs brought about by 5G technology.
Patent Information
- Application Number
- CN202510030298.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing ferrite electromagnetic wave absorption materials have problems such as limited reflection loss value, narrow effective absorption bandwidth, large density and thick matching thickness, which are difficult to meet the needs of electromagnetic wave pollution prevention and control brought about by 5G technology.
A microspherical high entropy spinel type ferrite absorbing material is used, which is a single-phase spinel structure with a micron-scale spherical morphology, with a chemical formula of MFe2O4, where M is Co, Ni, Cu, Zn, and Cr. Preparation through hydrothermal reaction and high-temperature calcination, etc., optimize the morphology and dielectric properties of the material.
It realizes efficient electromagnetic wave absorption of the material, has a small reflection loss value and a wide effective absorption bandwidth, and is simple in preparation and superior in performance.
Smart Images

Figure CN119822804A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a micro-spherical high-entropy spinel ferrite absorbing material and a preparation method thereof. Background Art
[0002] The popularization and development of 5G technology has brought about comprehensive coverage of electromagnetic wave-related technologies such as wireless communication technology and intelligent detection, making great contributions to people's lives, social development and national security. However, if the accompanying electromagnetic wave pollution is not prevented and controlled, it will cause information leakage, inaccurate operation of precision instruments and damage to human health.
[0003] Ferrite is widely used in the preparation of electromagnetic wave absorbing materials, but its limited reflection loss value and effective absorption bandwidth, as well as its large density and thick matching thickness mean that it often needs to be compounded with other materials. High entropy design and morphology control strategies can effectively improve the performance of pure ferrite absorbing materials. Summary of the invention
[0004] The purpose of the present invention is to provide a microspherical high entropy spinel ferrite absorbing material and a preparation method thereof, which can effectively improve the performance of pure ferrite absorbing material and has the characteristics of simple preparation, strong absorption performance and wide absorption frequency band.
[0005] To achieve the above object, the present invention provides a micro-spherical high entropy spinel ferrite absorbing material, wherein the micro-spherical high entropy spinel ferrite absorbing material is a single-phase spinel structure, presents a micron-scale spherical morphology, and has a chemical formula of MFe2O4;
[0006] Where M = Co, Ni, Cu, Zn, Cr.
[0007] Preferably, the minimum reflection loss value of the microspherical high entropy spinel ferrite absorbing material is -20 to -55 dB, and the effective absorption bandwidth is 3.0 to 6.0 GHz.
[0008] The present invention provides a method for preparing a microspherical high entropy spinel ferrite absorbing material, comprising the following steps:
[0009] S1. Weigh the raw materials respectively, dissolve them in deionized water, and mix them evenly to obtain a solution;
[0010] S2, weigh ammonium fluoride and add it to the solution obtained in S1, mix well, then add urea and stir until it is completely dissolved;
[0011] S3, the solution obtained in S2 is placed in a stainless steel high-pressure reactor, and placed in a blast drying oven to perform a hydrothermal reaction; after the reaction is completed, the solution is separated into solid and liquid, and the solid powder is washed to neutrality and collected to obtain a precursor;
[0012] S4. Place the precursor obtained in S3 in a corundum porcelain boat and calcine it in a high-purity nitrogen atmosphere to obtain a micro-spherical high-entropy spinel ferrite absorbing material.
[0013] Preferably, the raw materials weighed in S1 are Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cu(NO3)2·xH2O, Zn(NO3)2·9H2O and Cr(NO3)3·9H2O.
[0014] Preferably, the temperature of the hydrothermal reaction in S3 is 120-160° C., and the time is 6-24 hours.
[0015] Preferably, the conditions for high temperature calcination in S4 are: heating to 800-1100° C. at a heating rate of 2-10° C. / min and keeping the temperature for 1-5 hours.
[0016] Therefore, the present invention adopts the above-mentioned microspherical high-entropy spinel ferrite absorbing material and its preparation method, which can effectively improve the performance of pure ferrite absorbing material, and has the characteristics of simple preparation, strong absorption performance and wide absorption bandwidth.
[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is an XRD diagram of a microspherical high entropy spinel ferrite absorbing material and a high entropy oxide ceramic material obtained in Examples 1-4 of the preparation method thereof of the present invention;
[0019] Figure 2 This is a SEM image of a high-entropy oxide ceramic material obtained in Example 2 of a microspherical high-entropy spinel ferrite absorbing material and a preparation method thereof of the present invention;
[0020] Figure 3 This is a reflection loss curve of a high entropy oxide ceramic material obtained in Example 1 of a microspherical high entropy spinel ferrite absorbing material and a preparation method thereof of the present invention;
[0021] Figure 4 This is a reflection loss curve of a high entropy oxide ceramic material obtained in Example 2 of a microspherical high entropy spinel ferrite absorbing material and a preparation method thereof of the present invention;
[0022] Figure 5 This is a reflection loss curve of a high entropy oxide ceramic material obtained in Example 3 of a microspherical high entropy spinel ferrite absorbing material and a preparation method thereof of the present invention;
[0023] Figure 6This is a reflection loss curve of a high entropy oxide ceramic material obtained in Example 4 of a microspherical high entropy spinel ferrite absorbing material and a preparation method thereof of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0025] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0026] Example
[0027] The present invention provides a micro-spherical high-entropy spinel ferrite absorbing material. The micro-spherical high-entropy spinel ferrite absorbing material is a single-phase spinel structure, presents a micron-scale spherical morphology, and has a chemical formula of MFe2O4;
[0028] Wherein M=Co, Ni, Cu, Zn, Cr, the minimum reflection loss value of the microspherical high entropy spinel ferrite absorbing material is -20 to -55 dB, and the effective absorption bandwidth is 3.0 to 6.0 GHz.
[0029] The present invention provides a method for preparing a microspherical high entropy spinel ferrite absorbing material, comprising the following steps:
[0030] S1. Weigh Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cu(NO3)2·xH2O, Zn(NO3)2·9H2O and Cr(NO3)3·9H2O respectively, dissolve them in deionized water, and mix them evenly to obtain a solution, wherein the molecular weight of Cu(NO3)2·xH2O depends on its specific chemical formula and structure.
[0031] S2, weigh ammonium fluoride and add it to the solution obtained in S1, mix evenly, then add urea and stir until it is completely dissolved. As a morphology regulator, ammonium fluoride can regulate the nucleation and growth process of the crystal. In the process of preparing nanomaterials, it can help form a more uniform and regular morphology and improve the crystallinity of the material. The hydrolysis reaction of urea can adjust the pH value of the solution, which is conducive to the uniform nucleation and growth of high-entropy spinel ferrite, avoiding undesirable side reactions, and in the subsequent heat treatment process, the addition of urea can promote the low-temperature sintering of the material.
[0032] S3. The solution obtained in S2 is placed in a stainless steel high-pressure reactor and placed in a blast drying oven for hydrothermal reaction. The temperature of the hydrothermal reaction is 120-160°C and the time is 6-24 hours. After the reaction is completed, the solution is separated into solid and liquid, and the solid powder is washed to neutrality and collected to obtain a precursor. By adjusting the temperature and time of the hydrothermal reaction, the morphology and interface structure of the product can be flexibly controlled, providing more possibilities for optimizing the wave absorption performance of the material. In addition, adjusting the hydrothermal temperature and time can regulate the dielectric properties and magnetic properties of the material, providing more possibilities for optimizing the impedance matching performance and electromagnetic wave attenuation performance of the material.
[0033] S4. Place the precursor obtained in S3 in a corundum porcelain boat, and calcine it in a high-purity nitrogen atmosphere, heating it to 800-1100° C. at a heating rate of 2-10° C. / min and keeping it warm for 1-5 hours to obtain a microspherical high-entropy spinel ferrite absorbing material.
[0034] Example 1
[0035] S1. Dissolve 2mmol of Fe(NO3)3·9H2O, 0.1mmol of Co(NO3)2·6H2O, 0.3mmol of Ni(NO3)2·6H2O, 0.2mmol of Cu(NO3)2·xH2O, 0.2mmol of Zn(NO3)2·9H2O and 0.2mmol of Cr(NO3)3·9H2O in deionized water, and mix well to obtain a solution;
[0036] S2, weigh 332 mg of ammonium fluoride and add it to the solution obtained in S1, mix well, then add 1080 mg of urea and stir until it is completely dissolved;
[0037] S3, the solution obtained in S2 is placed in a stainless steel high-pressure reactor, and placed in a blast drying oven, and subjected to hydrothermal reaction at 120° C. for 8 hours; after the reaction is completed, the solution is subjected to solid-liquid separation, and the solid powder is washed to neutrality and collected to obtain a precursor;
[0038] S4. Place the precursor obtained in S3 in a corundum porcelain boat, calcine it in a high-purity nitrogen atmosphere, increase the temperature to 900°C at a heating rate of 5°C / min and keep it warm for 2 hours to obtain a microspherical high-entropy spinel ferrite absorbing material.
[0039] Figure 3 This is the reflection loss curve of the microspherical high entropy spinel ferrite absorbing material obtained in Example 1. It can be seen from the figure that the minimum reflection loss of the microspherical high entropy spinel ferrite absorbing material prepared in this example is -20.0dB, and the effective absorption bandwidth is 3.36GHz.
[0040] Example 2
[0041] S1. Dissolve 2mmol of Fe(NO3)3·9H2O, 0.1mmol of Co(NO3)2·6H2O, 0.3mmol of Ni(NO3)2·6H2O, 0.2mmol of Cu(NO3)2·xH2O, 0.2mmol of Zn(NO3)2·9H2O and 0.2mmol of Cr(NO3)3·9H2O in deionized water, and mix well to obtain a solution;
[0042] S2, weigh 332 mg of ammonium fluoride and add it to the solution obtained in S1, mix well, then add 1080 mg of urea and stir until it is completely dissolved;
[0043] S3, the solution obtained in S2 is placed in a stainless steel high-pressure reactor, and placed in a forced air drying oven, and subjected to hydrothermal reaction at 150° C. for 8 hours; after the reaction is completed, the solution is subjected to solid-liquid separation, and the solid powder is washed to neutrality and collected to obtain a precursor;
[0044] S4. Place the precursor obtained in S3 in a corundum porcelain boat, calcine it in a high-purity nitrogen atmosphere, increase the temperature to 900°C at a heating rate of 5°C / min and keep it warm for 2 hours to obtain a microspherical high-entropy spinel ferrite absorbing material.
[0045] Figure 2 This is the SEM image of the high entropy oxide ceramic material obtained in Example 2. It can be seen from the image that the prepared high entropy oxide ceramic is a microsphere composed of a large number of particles. Figure 4 This is the reflection loss curve of the microspherical high entropy spinel ferrite absorbing material obtained in Example 2. It can be seen from the figure that the minimum reflection loss of the microspherical high entropy spinel ferrite absorbing material prepared in this example is -41.5dB, and the effective absorption bandwidth is 3.52GHz.
[0046] Example 3
[0047] S1. Dissolve 2mmol of Fe(NO3)3·9H2O, 0.1mmol of Co(NO3)2·6H2O, 0.3mmol of Ni(NO3)2·6H2O, 0.2mmol of Cu(NO3)2·xH2O, 0.2mmol of Zn(NO3)2·9H2O and 0.2mmol of Cr(NO3)3·9H2O in deionized water, and mix well to obtain a solution;
[0048] S2, weigh 332 mg of ammonium fluoride and add it to the solution obtained in S1, mix well, then add 1080 mg of urea and stir until it is completely dissolved;
[0049] S3, the solution obtained in S2 is placed in a stainless steel high-pressure reactor, and placed in a forced air drying oven, and subjected to a hydrothermal reaction at 150° C. for 14 hours; after the reaction is completed, the solution is subjected to solid-liquid separation, and the solid powder is washed to neutrality and collected to obtain a precursor;
[0050] S4. Place the precursor obtained in S3 in a corundum porcelain boat, calcine it in a high-purity nitrogen atmosphere, increase the temperature to 900°C at a heating rate of 5°C / min and keep it warm for 2 hours to obtain a microspherical high-entropy spinel ferrite absorbing material.
[0051] Figure 5 This is the reflection loss curve of the microspherical high entropy spinel ferrite absorbing material obtained in Example 3. It can be seen from the figure that the minimum reflection loss of the microspherical high entropy spinel ferrite absorbing material prepared in this example is -29.4dB, and the effective absorption bandwidth is 4.48GHz.
[0052] Example 4
[0053] S1. Dissolve 2mmol of Fe(NO3)3·9H2O, 0.1mmol of Co(NO3)2·6H2O, 0.3mmol of Ni(NO3)2·6H2O, 0.2mmol of Cu(NO3)2·xH2O, 0.2mmol of Zn(NO3)2·9H2O and 0.2mmol of Cr(NO3)3·9H2O in deionized water, and mix well to obtain a solution;
[0054] S2, weigh 332 mg of ammonium fluoride and add it to the solution obtained in S1, mix well, then add 1080 mg of urea and stir until it is completely dissolved;
[0055] S3, the solution obtained in S2 is placed in a stainless steel high-pressure reactor, and placed in a forced air drying oven, and subjected to hydrothermal reaction at 150° C. for 20 hours; after the reaction is completed, the solution is subjected to solid-liquid separation, and the solid powder is washed to neutrality and collected to obtain a precursor;
[0056] S4. Place the precursor obtained in S3 in a corundum porcelain boat, calcine it in a high-purity nitrogen atmosphere, increase the temperature to 900°C at a heating rate of 5°C / min and keep it warm for 2 hours to obtain a microspherical high-entropy spinel ferrite absorbing material.
[0057] Figure 6 This is the reflection loss curve of the microspherical high entropy spinel ferrite absorbing material obtained in Example 4. It can be seen from the figure that the minimum reflection loss of the microspherical high entropy spinel ferrite absorbing material prepared in this example is -35.9 dB, and the effective absorption bandwidth is 5.44 GHz.
[0058] Figure 1This is the XRD diagram of the high entropy spinel ferrite prepared in Examples 1-4. It can be seen from the diagram that the prepared materials all have a single-phase spinel structure.
[0059] Therefore, the present invention adopts the above-mentioned microspherical high-entropy spinel ferrite absorbing material and its preparation method, which can effectively improve the performance of pure ferrite absorbing material, and has the characteristics of simple preparation, strong absorption performance and wide absorption bandwidth.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A microspherical high entropy spinel ferrite absorbing material, characterized in that: The microspherical high entropy spinel ferrite absorbing material is a single-phase spinel structure with a micron-scale spherical morphology, and its chemical formula is MFe2O4; Where M = Co, Ni, Cu, Zn, Cr.
2. The microspherical high entropy spinel ferrite absorbing material according to claim 1, characterized in that: The microspherical high entropy spinel ferrite wave absorbing material has a minimum reflection loss value of -20 to -55 dB and an effective absorption bandwidth of 3.0 to 6.0 GHz.
3. A method for preparing a microspherical high entropy spinel ferrite absorbing material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Weigh the raw materials respectively, dissolve them in deionized water, and mix them evenly to obtain a solution; S2, weigh ammonium fluoride and add it to the solution obtained in S1, mix well, then add urea and stir until it is completely dissolved; S3, placing the solution obtained in S2 into a stainless steel high-pressure reactor and placing it in a forced air drying oven for hydrothermal reaction; After the reaction is completed, the solution is separated into solid and liquid, and the solid powder is washed to neutrality and collected to obtain a precursor; S4. Place the precursor obtained in S3 in a corundum porcelain boat and calcine it in a high-purity nitrogen atmosphere to obtain a microspherical high-entropy spinel ferrite absorbing material.
4. The method for preparing a microspherical high entropy spinel ferrite absorbing material according to claim 3, characterized in that: The raw materials weighed in S1 are Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cu(NO3)2·xH2O, Zn(NO3)2·9H2O and Cr(NO3)3·9H2O.
5. The method for preparing a microspherical high entropy spinel ferrite absorbing material according to claim 3, characterized in that: The temperature of the hydrothermal reaction in S3 is 120-160° C. and the time is 6-24 hours.
6. The method for preparing a microspherical high entropy spinel ferrite absorbing material according to claim 3, characterized in that: The conditions for high temperature calcination in S4 are: heating to 800-1100° C. at a heating rate of 2-10° C. / min and keeping the temperature for 1-5 hours.
Citation Information
Patent Citations
High-entropy spinel wave-absorbing ceramic material and preparation method thereof
CN116239376A
High-entropy oxide ceramic material as well as preparation method and application thereof
CN116768614A